IN-STORE MEDIA: HOW EFFECTIVE ARE THEY? EVIDENCE FROM THE PHILIPPINES - Gutierrez, Ben Paul (Philippine Management Review; Vol 15 (2008), 2009)
This paper investigates the effectiveness of an in-store radio in urban Philippines. Measures of international in-store media effectiveness studies are first reviewed. Then, this study replicates the Arbitron Retail Audio study using a sample of 600 Filipino shoppers who were interviewed to obtain shopper perceptions, attitudes toward instore radio and the corresponding effect on purchase behavior. Implications about making in-store media more effective are described at the end of the paper.
Keywords: marketing communication, in-store media effectiveness, shopper marketing, in-store radio